2021
DOI: 10.3390/app11167331
|View full text |Cite
|
Sign up to set email alerts
|

Debris Removal by Activation of Endodontic Irrigants in Complex Root Canal Systems: A Standardized In-Vitro-Study

Abstract: Aim of the study was to develop a standardized model system to investigate endodontic irrigation techniques and assess the efficiency of different activation methods on the removal of hard tissue debris in complex root canal systems. Mesial roots of mandibular molars were firstly scanned by micro-computed tomography (µCT) and allocated to three groups of irrigant activation: sonic activation (EDDY, VDW, Munich, Germany), laser activation (AutoSWEEPS, FOTONA, Ljubljana, Slovenia) and conventional needle irrigat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Firstly, anatomical variations such as the dimensions of root canals and isthmuses have an impact on AHTD removal as penetration of the irrigant is reduced in narrow isthmuses [ 62 ]. To overcome anatomical variations, 3D-printed root canal models were recently introduced to allow a reproducible and standardized assessment of different irrigation techniques [ 72 , 75 ]. However, substitution of dentine by artificial root canals may also affect irrigant penetration since the surface properties of dentine are different from those of hydrophobic resins [ 56 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, anatomical variations such as the dimensions of root canals and isthmuses have an impact on AHTD removal as penetration of the irrigant is reduced in narrow isthmuses [ 62 ]. To overcome anatomical variations, 3D-printed root canal models were recently introduced to allow a reproducible and standardized assessment of different irrigation techniques [ 72 , 75 ]. However, substitution of dentine by artificial root canals may also affect irrigant penetration since the surface properties of dentine are different from those of hydrophobic resins [ 56 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of LAI is based on cavitation, a physical phenomenon that induces the formation and implosion of vapor bubbles at the fiber tip, causing very rapid fluid movement in the canal [25,26]. LAI has been shown to have a greater efficacy in the removal of canal debris and greater antibacterial effect than other activation techniques [44][45][46]. For LAI to be effective, the high absorption of laser energy into the irrigating liquid is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…According to their study, another advantage of the SWEEPS technique is that the in-and-out movement of the liquid, which resembles inhalation and exhalation, generates alternating shear stresses in the root canal, which plays a pivotal role in improving the quality of the debridement process. No risk of intracanal instrument fracture is another advantage of the SWEEPS technique, since in this technique the tip of the handpiece is positioned in the access cavity and above the root canals, whereas in sonic and ultrasonic techniques, the instrument is introduced into the canal and proceeds to the apex for the activation of the intracanal irrgant [28]. In addition, a previous study has shown that photosensitizer extrusion is not harmful [29].…”
Section: Discussionmentioning
confidence: 99%